SENTIMENT ANALYSIS OF COVID-19 VACCINATION POSTS ON FACEBOOK IN INDONESIA WITH CROWDTANGLE - Adita Rianto; Ahmad Rafie Pratama (Kresnamedia Publisher, 2021)
COVID-19 was declared a pandemic by the World Health Organization (WHO) in early 2020. The Indonesian government has taken steps to stop COVID-19 from spreading, one of which is vaccination. However, not everyone thinks vaccination is a good idea. Like in other countries, Indonesian people responded in different ways to COVID-19 vaccination posts on social media, be it from government officials or news portals. Public responses can be used to help the government make a better vaccination strategy to end the pandemic in Indonesia. Using the lexicon method in determining the sentiment in COVID-19 vaccination posts on Facebook, this research found that unlike news portals that tended to post a more balanced content (36% positive, 20% negative, and 44% neutral out of 23,623 posts, min score = -19, max score = 24, mean = 0.25, SD = 1.43), government accounts posted much more positive content, both in quality (min score = -15, max score = 40, mean score = 4.16, SD = 6.76 ) and quantity (69% positive) than they did the neutral (15%) and the negative content (16%) out of 723 posts. Subsequent analysis with Two-Way ANOVA tests discovered that COVID-19 vaccination posts by the news portals elicited more varied reactions from the public than government accounts that tended to elicit mostly positive reactions. Also, both the content sentiment of COVID-19 vaccination posts in Indonesia and the account types making those posts, as well as their interaction terms do have an impact on how the public responds to them.